MENGOPTIMALKAN SELF MANAGEMENT SEBAGAI UPAYA MENUMBUH KEMBANGKAN KEGIATAN PEMBELAJARAN MATA PELAJARAN EKONOMI DI SEKOLAH MENENGAH ATAS - Adi Suprayitno (Universitas PGRI Madiun, 2014)
Self-Management represent therapy technique form of behavior/behavioral. Therapy form of behavior this focus study to individual to become effective changer this for behavior will own. technique of Self-Management this cover: self-monitoring, self-evaluation, and self-reinforcement. Third the technique aim to be behavioral to to increase learn Senior High School student. Learn SMA beside as instructor, also as coach and counsellor. As counsellor, teacher share to assist process learn by creating the condition of conducive student able to alter its own behavior and also can solve internal issues activity of study economic subject. Problem of which often experienced of to relate to process learn namely student do not want to enquire if/when meeting items which is difficult to be comprehended, and in disregard of student question of items studied. To overcome problems of student, can be developed technique of self-management. Stages;Steps mentioned as following: ( 1) planning and executing distorting technique; ( 2) evaluating distorting program.